The Energy of Muscle Contraction. II. Transverse Compression and Work - Ryan, David S.; Domínguez, Sebastián; Ross, Stephanie A.; Nigam, Nilima; Wakeling, James M. (Frontiers in Physiology, 2020)
In this study we examined how the strain energies within a muscle are related to changes in longitudinal force when the muscle is exposed to an external transverse load. We implemented a three-dimensional finite element model of contracting muscle, using the principle of minimum total energy and allowing the redistribution of energy through different strain energy-densities. T; this allowed us to determine the importance of the strain energy-densities to the transverse forces developed by the muscle. We ran a series of in silica experiments on muscle blocks varying in initial pennation angle, muscle length, and external transverse load . As muscle contracts it maintains a near constant volume. As such, any changes in muscle length are balanced by deformations in the transverse directions such as muscle thickness or muscle width. Muscle develops transverse forces as it expands. In many situations external forces workact to counteract these transverse forces and the muscle responds to external transverse loads while both passive and active. The muscle blocks used in our simulations decreased in thickness and pennation angle when passively compressed and pushed back on the load when they were activated. Activation of the compressed muscle blocks led either to an increase or decrease in muscle thickness depending on whether the initial pennation angle was less than or greater than 15°, respectively. Furthermore, the strain energy increased and redistributed across the different strain-energy potentials during contraction. The volumetric strain energy-density varied with muscle length and pennation angle and was reduced with greater transverse load for most initial muscle lengths and pennation angles. For muscle blocks with initial pennation angles 020° the reduction in longitudinal muscle force occurred largely because of a reduction in volumetric strain energy-density. External transverse load reduced the longitudinal muscle force for initial pennation angles of 0=0°. For pennate muscle, changes in longitudinal force (increase or decrease) depended on the muscle length, pennation angle and the direction of the external load relative to the muscle fibres.